A Novel Technique for Exeter Stem Extraction. Issue 1 (March 2019) - MacDonald, David R.W.; Harper, Lauren; Mitchell, Martin
Abstract : We describe a new technique for extraction of the Exeter V40 stem using the readily available Exeter offset broach handle. Abstract : Supplemental Digital Content is available in the text.